Opening of Epithelial Tight Junctions and Enhancement of Paracellular Permeation by Chitosan: Microscopic, Ultrastructural, and Computed-Tomographic Observations - Sonaje, Kiran; Chuang, Er-Yuan; Lin, Kun-Ju; Yen, Tzu-Chen; Su, Fang-Yi; Tseng, Michael T; Sung, Hsing-Wen (Molecular pharmaceutics, 2012)
This study investigates the effects of chitosan (CS) on the opening of epithelial tight junctions (TJs) and paracellular transport at microscopic, ultrastructural, and computed-tomographic levels in Caco-2 cell monolayers and animal models. Using immunofluorescence staining, CS treatment was observed to be associated with the translocation of JAM-1 (a trans-membrane TJ protein), resulting in the disruption of TJs; the removal of CS was accompanied by the recovery of JAM-1. Ultrastructural observations by TEM reveal that CS treatment slightly opened the apical intercellular space, allowing lanthanum (an electron-dense tracer) to stain the intercellular surface immediately beneath the TJs, suggesting the opening of TJs. Following the removal of CS, the TJs were completely recovered. Similar microscopic and ultrastructural findings were obtained in animal studies. CS nanoparticles were prepared as an insulin carrier. The in vivo fluorescence-microscopic results demonstrate that insulin could be absorbed into the systemic circulation, while most CS was retained in the microvilli scaffolds. These observations were verified in a biodistribution study following the oral administration of isotope-labeled nanoparticles by single-photon emission computed tomography. Above results reveal that CS is a safe permeation enhancer and is an effective carrier for oral protein delivery.